Factors Affecting the Performance of the Communicator in Health Media and its Digital Platforms and the Attitudes of the Public Towards it: A Field Study - Victoria-Mas, Juan Salvador; Alshammari, Mohammad (Al Arabia Public Relations Agency, 2023)
The global interest in studying the professional and ethical orientations of the communicator in general has increased, and this has been relatively reflected in the Kingdom as a result of the emergence of new media outlets. In addition, this causes the communicator to experience an ongoing situation of uncertainty, despair, frustration, etc., and has led to the emergence of new occupational diseases and the increase of psychological and nervous pressures in addition to their repercussions on the performance of the media professionals themselves as one of the most important external factors affecting the health media policy through which the communicator works, which in turn is reflectedin the performance of the communicators’ professional and functional roles.
Keywords: Medios de comunicación social; Condiciones de trabajo; Riesgos para la salud - Comunicación; Opinión pública - Arabia Saudí; Health media policy; Digital platforms; Communicator orientations; Public attitudes in Saudi Arabia